If it's not what You are looking for type in the equation solver your own equation and let us solve it.
44-f=50-2f
We move all terms to the left:
44-f-(50-2f)=0
We add all the numbers together, and all the variables
-f-(-2f+50)+44=0
We add all the numbers together, and all the variables
-1f-(-2f+50)+44=0
We get rid of parentheses
-1f+2f-50+44=0
We add all the numbers together, and all the variables
f-6=0
We move all terms containing f to the left, all other terms to the right
f=6
| -5x+2x-2=23 | | -9=5n/17 | | -x+257=174 | | 11d+4=19+12d | | 9-h/4=10 | | 5+8x-1.5=5 | | 12k=20+7k | | -2x26=x−13 | | 0=4·2x | | 12z-4z=-8z | | -5a+27=-33 | | 9x+13+10+15=180 | | 15/z=6/21 | | 9h+5=777 | | 5(u+)-u=4(u-1)+9 | | 2(7-2y)=9 | | 3(x+3)=2x+20 | | 1=253-u | | 7n-6=33 | | 10=0.5x-4 | | -98=-29(1+8m) | | (n+10)=8 | | 16y-5=17y | | x²=3600 | | 7v=-23 | | 87-y=190 | | 5(3x+4)+8=105 | | K-18=4K-5k+12 | | -n/8-4=2 | | −6x+10+8x=12−4x−6x+10+8x=12−4x. | | 2y-5y=3y-12 | | 1=253*u |